Indication of zoonyms in idiomatic phrases (Based on the Chinese and Kazakh phraseologisms) (Journal of Oriental Studies, 2018)
This article discusses the cultural semantics of phraseological units ofKazakh and Chinese languages. The study led to the conclusion that thevalue-semantic aspect of the mentality of the people is nothing but thetotality of systematized knowledge and ideas of people about the environmentand the world, which are considered through the prism of their socialand emotional experience.